Water quality evaluation using water quality index and pollution model in selected communities in Gbaramatu Kingdom, Niger Delta, Nigeria - Sam, Kabari; Onyena, Amarachi Paschaline; Eriegha, Ochuko Joshua; Eze, Felix (African Journal of Environmental Science and Technology, 2023)
Drinking water quality is a critical factor affecting human health particularly in natural resource-dependent countries including Nigeria. Hydrocarbon related pollution, mining waste, microbial load, industrial discharge and other anthropogenic stressors degrade drinking water quality in coastal communities and pose serious public health and ecological risks. This study evaluated the physicochemical properties of drinking water in selected communities (Okerenkoko, Kurutie, and Oporoza) located in Gbaramatu Kingdom, in the Niger Delta region of Nigeria, in order to assess the water quality using the Water Quality Index (WQI) and pollution models. Nitrate, Chromium, Cadmium, Copper, Lead, Aluminium, pH, Total Hardness, Total Dissolved Solids, Cyanide, and Residual Chlorine were measured in twelve selected locations across the three communities. The WQI results of the analyzed water samples in the area indicated that they exceeded the critical WQI value of 100, with a mean pH of 8.11 ± 0.32, indicating unsuitability for consumption. Nickel ranging from 0.014 to 0.176 mg/L and residual chlorine 11.6 to 7407 mg/L were the major contributors to the degradation of water quality and exceeded the WHO recommended limit of 0.02 and 0.25 respectively. While groundwater had better organoleptic properties compared to surface and rain water, the geo-accumulation index showed that water sources in the area vary from moderately to heavily contaminated with Ni and Cd. These WQI and pollution model results necessitate an urgent response from local stakeholders to address the water quality deterioration, such as providing alternative water supplies, to minimize the potential health risks to the local population.
Keywords: Water quality index; contamination index; oil pollution; chemical parameters; geo-accumulation index.